Morphometry of distal radius – a radiographic study in Nepalese population - Dawadi, Tej Prakash; Regmi, Ananda Prasad; Sitaula, Jyoti; Neupane, Gaurav; Sharma, Bishnu Dev; Rijal, Sanjeeb; Basel, Suman; Timalsina, Santosh; Panthi, Prabha (Journal of Chitwan Medical College, 2022)
Background: Distal radius fractures are common injuries. The outcome of the fractures depends upon the post reduction morphometric parameters. This study was aimed to assess the normal morphometric parameters of distal radius in Nepalese population. Methods: This was a prospective cross-sectional study of morphometric measurements of 150 distal radius on x rays of wrist joints of patients presenting to department of orthopedics at CMCTH from October 2020 to September 2021. Radial height, Radial inclination, Palmer tilt, Ulnar variance and Radial width in posteroanterior (PA) and lateral views were measured. The data obtained was analyzed to see the difference according to age, sex, side, dominance and ethnicity. Results: The mean values of Radial height, Radial inclination, Palmer tilt, Ulnar variance and Radial width posteroanterior and lateral were 11.75+-0.94mm, 22.75+-1.50 degrees, 10.51+-1.04 degrees, -0.51 to+-1.15 mm, 27.05+-1.16 mm and 18.7+-1.12 mm respectively. Conclusions: The distal radius morphometry of Nepalese population is comparable to other national, regional and western similar studies. There were no any statistically significant differences of all the morphometric parameters of distal radius according to age, sex, side, dominance and ethnicity except Radial inclination, according to ethnicity; and Radial width, according to ethnicity and dominance.